2013
DOI: 10.3109/09637486.2013.798268
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological use of ellagic acid-rich pomegranate fruit

Abstract: In recent years, the therapeutic use of non-drug substances such as herbal and medicinal foods is increasing progressively. Of these substances, Punica granatum L., which is an ancient and highly distinctive fruit, has been proposed for treatment of several different illnesses. Ellagic acid (EA) is one of those biological molecules found in pomegranate and may have therapeutic potential in many diseases. EA has been detected not only in pomegranate but also in a wide variety of fruits and nuts such as raspberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…An analysis of the antioxidant activity of various dietary supplements has shown that the antioxidant activity of pomegranate juice exceeds that of orange juice (Parashar, ), milk thistle, green tea, grape seed, goji, acai (Henning et al ., ) and infusions of red wine or green tea (Gil et al ., ). In addition to antioxidant function, EA and punicalagins in pomegranate have been implicated as potent anticancer and antiatherosclerotic agents (Adams et al ., ; Viuda‐Martos et al ., ; Usta et al ., ). Although the potential health benefits of punicalagins have been recognized, their biosynthesis has not yet been thoroughly characterized.…”
Section: Discussionmentioning
confidence: 97%
“…An analysis of the antioxidant activity of various dietary supplements has shown that the antioxidant activity of pomegranate juice exceeds that of orange juice (Parashar, ), milk thistle, green tea, grape seed, goji, acai (Henning et al ., ) and infusions of red wine or green tea (Gil et al ., ). In addition to antioxidant function, EA and punicalagins in pomegranate have been implicated as potent anticancer and antiatherosclerotic agents (Adams et al ., ; Viuda‐Martos et al ., ; Usta et al ., ). Although the potential health benefits of punicalagins have been recognized, their biosynthesis has not yet been thoroughly characterized.…”
Section: Discussionmentioning
confidence: 97%
“…Catechin is biosynthesized in various plants; for instance, it was reported as the main phenolic in soluble fraction of finger millet grains (up to 1611 ± 87 mg/g defatted meal) (Chandrasekara & Shahidi, 2011). Ellagic acid (EA) is one of the bioactive molecules found in a wide variety of fruits and nuts such as pomegranates (Usta, Ozdemir, Schiariti, & Puddu, 2013), raspberries (Bobinaitė , Viškelis, & Venskutonis, 2012), nuts (De la Rosa et al, 2014;John & Shahidi, 2010), and may have therapeutic potential in many diseases. For instance, most recently ellagic acid was shown to inhibit aldose reductase which may be associated with the implications for prevention of diabetic complications (Akileshwari et al, 2014).…”
Section: Identification and Quantitative Analysis Of Flavonoids And Pmentioning
confidence: 99%
“…Pomegranate (Punica granatum L.) is a rich source of phytochemicals, mainly anthocyanins, ellagitannins (punicalin, punicalagin, pedunculagin) and ellagic acid with antioxidant, anticancer and cardiovascular protective activities (Medjakovic and Jungbauer 2013;Usta et al 2013). Pomegranate has also been studied for its anti-diabetic properties.…”
Section: Introductionmentioning
confidence: 99%